Saturnino de Brito (1864-1929) e as águas de São Paulo: melhoramentos do Rio Tietê - Nery, Márcia Iara Guedes (2023)
Francisco Saturnino Rodrigues de Brito (1864-1929), dedicated engineer, above all, to issues of basic sanitation, contributed significantly to the urban plans of several brazilian cities. He was a member, as chief engineer, of the Sanitation Commission of the State of São Paulo, leading the Tietê river Improvements project, plan focused on the waters of the great metropolis. Quite astute, brought innovative solutions to the problems of the city in the First Republic. The ideas, however, were not implemented as envisaged in the initial project and some questions carefully analyzed by him remain as problems currently unresolved